Formação continuada do professor de língua materna na olimpíada de língua portuguesa: uma perspectiva decolonial - Legramandi, Aline Belle (2019)
Since the 1990s, the influence of international regulatory agencies (World Bank, ECLAC, OECD and UNESCO) on the orientation of educational policies through reports and recommendations, which have leveraged public-private partnership in education systems, is undoubted. The Portuguese Language Olympics Writing the Future (OLPEF) is a continuing teacher education program provided by the Ministry of Education (MEC) and Fundação Itaú. This continuing education program adopts such recommendations, European teaching methodology and concepts from the financial market and which privileges the predominance of a hegemonic curriculum, outside schools, outside the knowledge of teachers and outside the context that should be based on its elaboration. Given the above, the OLPEF becomes a potential target for study on the epistemological and political hegemonic incidence in educational public policies. Thus, the object of this research is the continuing education of mother tongue teachers through governmental instruments and has as its guiding question: what are the conceptions of mother tongue teachers about continuing education through notebooks provided by OLPEF? The objective of this study was to analyze the conceptions of native language teachers on continuing education through the notebooks provided by OLPEF and, as specific objectives, a) understand the nature of the principles that govern the program: hegemonic or counter-hegemonic; b) know the structuring principles, operationalization and purposes of the Portuguese Language Olympics Writing the Future; c) examine whether teachers detect emancipatory perspectives on program principles; d) to verify if the teachers who adhere to the program identify the existence of reproduction of the dominant culture and knowledge. The theoretical framework, which reconciles historical-dialectical materialism with decolonial theories, was built in such a way as to adhere to the object to achieve the objectives described above and serve as a contribution to the core category of this research, the continuing education of teachers. The methodology adopted in this research is the qualitative approach and makes use of the interview as a data collection instrument. The data were collected in the documents that legislate and guide the continuous formation of teachers, in the documents and in the notebook used by the teachers for teaching and learning the opinion article genre and in the speeches that portray the conceptions of the participants of this program. To assist in the analysis and interpretation of data, the discourse analysis technique of Mikhail Bakthin was adopted.